Calculation Model of Time-varying Meshing Stiffness of Planet Gear Pitting Fault based on Full Tooth Profile - Chaoyang Jiang; Yanxue Wang; Junjie Lai (Jixie chuandong)
When a gear has a pitting fault，the vibration response characteristics caused by its time-varying meshing stiffness change is an important basis for the diagnosis of pitting faults，and an accurate gear geometry model is of great significance for the calculation accuracy of the gearing time-varying meshing stiffness. The tooth profile equations of internal and external meshing gears are derived，and a time-varying meshing stiffness calculation model of planetary gear pitting failure based on full tooth profile is proposed，which effectively solves the problem of the need for tooth number judgment and poor accuracy in the simplified model. The calculation accuracy of time-varying meshing stiffness of gear is improved. A theoretical foundation is laid for the dynamics modeling， failure mechanism analysis and fatigue life analysis of gear pitting failure.